Analisis historis stratifikasi sosial dan pembatasan perkawinan dalam masyarakat batak angkola kota Padang Sidempuan - Yusrida Yusrida; Sakti Ritonga (IICET (Indonesian Institute for Counseling, Education and Therapy), 2024)
This research aims to analyze social stratification and marriage restrictions in the Angkola Batak community in Padang Sidempuan City. The focus of the research included the influence of historical factors on the social structure and norms governing marriage in the community. The research informants totaled 5 people, consisting of community leaders, traditional leaders, and family members involved in the marriage process. The method used in this research is a qualitative approach with in-depth interview techniques and participatory observation. The theory underlying this research is Max Weber's social stratification theory, which examines the relationship between social class, status and power in a cultural context. The research findings show that social stratification in the Angkola Batak community is strongly influenced by economic, educational and traditional factors. In addition, there are restrictions on marriage that are influenced by customary norms and beliefs rooted in the history of the Batak community. The novelty of this research lies in combining historical analysis with contemporary social studies that provide new insights into social dynamics in the Angkola Batak community. Limitations of the research include the relatively small number of informants and the possibility of subjective bias in data collection. This research is expected to serve as a basis for further research on social and cultural issues in the Angkola Batak community and other regions in Indonesia.